Three is a Magic Number: Evidence on the Effects of the Application of the Three-Point Rule in Italy's Serie A. (April 2021) - Alfano, Vincenzo; Cicatiello, Lorenzo; Gaeta, Giuseppe Lucio; Gallo, Michele; Rotondo, Francesca
This paper contributes to the expanding literature that investigates the effects of the introduction of a three-points-for-a-win rule in football. To this end, it provides empirical evidence of the effect of the rule on Italy's most prestigious football league. Our analysis uses data collected over a long period of time and relies on pooled regressions and a regression discontinuity design. The findings provide evidence that in the case of the Italian league the rule worked as expected, unlike what previous contributions have found when looking at other national football leagues.